2003
DOI: 10.1680/ensu.2003.156.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an oil interceptor incorporated into a pervious pavement

Abstract: The use of pervious pavements is an important technique used for source control in sustainable drainage systems (SUDS) that allows water to infiltrate into hard surfaces and then slowly releases it to either a drainage outlet or into the ground. SUDS also remove low levels of pollution from the water by filtration and biodegradation of hydrocarbons that are adsorbed to materials within the construction. Current pervious pavement systems are not used in locations where the risk of pollution occurring is high or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Due to many economic advantages, construction waste bricks are cheaper than other alternative adsorbents, such as activated carbon, natural and synthetic zeolites, and ion exchange resins. Wilson et al showed that concrete blocks, crushed stone beds, and geotextiles in the permeable paving system can retain hydrocarbon contaminants and improve the quality of effluent [4]. Wang et al confirmed that using construction wastes as bioretention media can remove 90% of heavy metals in rainwater [1].…”
Section: Introductionmentioning
confidence: 99%
“…Due to many economic advantages, construction waste bricks are cheaper than other alternative adsorbents, such as activated carbon, natural and synthetic zeolites, and ion exchange resins. Wilson et al showed that concrete blocks, crushed stone beds, and geotextiles in the permeable paving system can retain hydrocarbon contaminants and improve the quality of effluent [4]. Wang et al confirmed that using construction wastes as bioretention media can remove 90% of heavy metals in rainwater [1].…”
Section: Introductionmentioning
confidence: 99%
“…After the initial 3 months, the oil and RS were applied to the test rig surface at monthly intervals at rates of 25 mL/m (using a calibrated syringe) and 21 g/m respectively. The oil volume was well in excess of that reported by [ 16 ] as typically associated with storm water runoff (<0.1 g/L) and the RS used was double that reported by [ 17 ] of up to 12.6 g/m from a “dirty” road; this value has also been used in previous laboratory simulation experiments [ 18 ]. At the end of the monitoring period, a total of 367.5 g RS and 430 mL oil had been applied, thus representing a worst-case scenario, probably reflecting a highly contaminated industrial or heavily trafficked site.…”
Section: Methodsmentioning
confidence: 55%